Inovasi Sistem Pengeringan Kopi dengan Teknologi Solar Dryer Modular Berbasis EBT sebagai Solusi Krisis Iklim di Desa Pajahan Kabupaten Tabanan - I Putu Sugiantara; Komang Desky Ari Antara; Chandra Bintang Lumban Siantar; I W. Arta Wijaya; Ni Made Gusmiari Ayunda Krisnayani; I Made Krisna Dhira Mulyana (Lembaga Pengembangan Kinerja Dosen, 2025)
Pajahan Village is one of the villages in Pupuan District, Tabanan Regency which is located at an altitude of 800-1500 m above sea level with coffee plantations as the main commodity. However, coffee farmers in Pajahan Village complained of erratic climatic conditions that hindered coffee farmers in terms of drying their coffee beans. In this workaround, some farmers choose to dry their coffee beans outside districts such as Buleleng Regency. But of course this will add to production costs, transportation costs and the time needed to dry coffee beans. Through one of the Merdeka Belajar Kampus Merdeka programs, namely Bina Desa, the Electrical Student Association provides a solution, namely by procuring a Modular Solar Dryer with a capacity of 40 kilograms / tool with the aim of being able to reduce production and transportation costs needed while saving time needed in post-harvest coffee bean processing. In addition to the procurement of tools, the Village Development Team of the Electrical Student Association also held a workshop to provide knowledge to Pajahan Village coffee farmers by presenting speakers from Bali Mall. In addition, program support was also held such as mass media publications, guidebooks on the use and maintenance of Solar Dryers, as well as posters, and videos of activities.